A Strategy to Prevent and Control Zoonoses? - Lei, Ruipeng (Hastings Cent Rep, 2020)
The authors argue that in preventing and controlling the pandemic of Covid‐19, we should have taken an offensive or proactive strategy rather than a defensive or reactionary one because the former type of approach can bring about more health benefits and fewer harms than can the latter. The offensive or proactive approach consists of two parts: The first part is to preemptively establish a barrier between a novel virus and humans in order to prevent the spillover of the virus into humans, and the second part is that, when a spillover fails to be prevented, we should take public interventions, such as contact tracing, social distancing, and quarantine and isolation, as early as when there are several dozens or one hundred or more cases that manifest symptoms with an unknown etiology in order to prevent an epidemic that is still limited to relatively small groups from developing into an outbreak.